Advancing Energy-Efficient Technologies in the Internet of Things (IoT): A Comprehensive Analysis - Kaban, Roberto (JCEIT: Journal of Computer Engineering and Information Technology, 2025)
In the era of the Internet of Things (IoT), energy efficiency has become one of the primary research focuses. This study explores five Scopus-indexed papers in the Q1 and Q2 categories, published between 2022 and 2024. The selected papers discuss various strategies to enhance energy efficiency in the IoT context. This review provides a comprehensive overview of the latest efforts in delivering energy-efficient solutions to support the growth and sustainability of IoT. Resource optimization, both in wireless communication infrastructure and data management, is a crucial step in fostering an environmentally friendly IoT ecosystem. Through innovative approaches and intelligent resource optimization, IoT has significant potential to become more energy-efficient and contribute to global environmental sustainability goals. REFERENCES Abdul-Qawy, A. S. H., S. Almurisi, N. M., & Tadisetty, S. (2020). Classification of Energy Saving Techniques for IoT-based Heterogeneous Wireless Nodes. Procedia Computer Science, 171, 2590–2599. https://doi.org/10.1016/j.procs.2020.04.281 Aldin, H. N. S., Ghods, M. R., Nayebipour, F., & Torshiz, M. N. (2024). A comprehensive review of energy harvesting and routing strategies for IoT sensors sustainability and communication technology. Sensors International, 5, 100258. https://doi.org/10.1016/j.sintl.2023.100258 Al-Mutawa, R. F., & Albouraey, F. (2020). A Smart Home System based on Internet of Things. International Journal of Advanced Computer Science and Applications, 11(2). https://doi.org/10.14569/IJACSA.2020.0110234 Alsoufi, M. A., Razak, S., Siraj, M. M., Nafea, I., Ghaleb, F. A., Saeed, F., & Nasser, M. (2021). Anomaly-Based Intrusion Detection Systems in IoT Using Deep Learning: A Systematic Literature Review. Applied Sciences, 11(18), 8383. https://doi.org/10.3390/app11188383 Geetha, S., & Gouthami, S. (2016). Internet of things enabled real time water quality monitoring system. Smart Water, 2(1), 1. https://doi.org/10.1186/s40713-017-0005-y Khan, M. N. U., Cao, W., Tang, Z., Ullah, A., & Pan, W. (2024). Energy-Efficient De-Duplication Mechanism for Healthcare Data Aggregation in IoT. Future Internet, 16(2), 66. https://doi.org/10.3390/fi16020066 Macedo, E. L. C., De Oliveira, E. A. R., Silva, F. H., Mello, R. R., Franca, F. M. G., Delicato, F. C., De Rezende, J. F., & De Moraes, L. F. M. (2019). On the security aspects of Internet of Things: A systematic literature review. Journal of Communications and Networks, 21(5), 444–457. https://doi.org/10.1109/JCN.2019.000048 Milarokostas, C., Tsolkas, D., Passas, N., & Merakos, L. (n.d.). A Comprehensive Study on LPWANs With a Focus on the Potential of LoRa/LoRaWAN Systems. Moutaib, M., Ahajjam, T., Fattah, M., Farhaoui, Y., Aghoutane, B., & El Bekkali, M. (2021). Optimization of the Energy Consumption of Connected Objects. International Journal of Interactive Mobile Technologies (iJIM), 15(24), 176–190. https://doi.org/10.3991/ijim.v15i24.26985 O’Dwyer, E., Pan, I., Charlesworth, R., Butler, S., & Shah, N. (2020). Integration of an energy management tool and digital twin for coordination and control of multi-vector smart energy systems. Sustainable Cities and Society, 62, 102412. https://doi.org/10.1016/j.scs.2020.102412 Ogbebor, J. O., Imoize, A. L., & Atayero, A. A.-A. (2020). Energy Efficient Design Techniques in Next-Generation Wireless Communication Networks: Emerging Trends and Future Directions. Wireless Communications and Mobile Computing, 2020, 1–19. https://doi.org/10.1155/2020/7235362 Politi, B., Foucaran, A., & Camara, N. (2022). Low-Cost Sensors for Indoor PV Energy Harvesting Estimation Based on Machine Learning. Energies, 15(3), 1144. https://doi.org/10.3390/en15031144 Sebestyen, H., Popescu, D. E., & Zmaranda, R. D. (2025). A Literature Review on Security in the Internet of Things: Identifying and Analysing Critical Categories. Computers, 14(2), 61. https://doi.org/10.3390/computers14020061 Tan, F., Pang, S., Cao, Y., Chen, H., & Lv, T. (2024). Energy-Efficient Device-to-Device Communications for Green Internet of Things Using Unmanned Aerial Vehicle-Mounted Intelligent Reflecting Surface. Drones, 8(4), 122. https://doi.org/10.3390/drones8040122 Wu, Y., Lu, P., Bu, X., Liu, S., Zhong, C., & Liu, C. (2022). Computing offloading method with low power consumption constraint for smart grid. Journal of Physics: Conference Series, 2215(1), 012010. https://doi.org/10.1088/1742-6596/2215/1/012010 Xie, J., Chang, Z., Guo, X., & Hamalainen, T. (2023). Energy Efficient Resource Allocation for Wireless Powered UAV Wireless Communication System With Short Packet. IEEE Transactions on Green Communications and Networking, 7(1), 101–113. https://doi.org/10.1109/TGCN.2022.3218314